Exploring local realities: Perceptions and experiences of healthcare workers on the management and control of drug-resistant tuberculosis in Addis Ababa, Ethiopia - Mussie, Kirubel Manyazewal; Yimer, Solomon Abebe; Manyazewal, Tsegahun; Gradmann, Christoph (PloS one, 2019)
Drug-resistant tuberculosis (DR-TB) remains a major health security threat worldwide. The effectiveness of implementation of DR-TB control strategies has been a subject of research and controversy. In resource-limited settings, using conventional medicine as the only framework to explain DR-TB gives a rather incomplete picture of the disease. This study intended to explore the perceptions and experiences of healthcare workers on the management and control of DR-TB in Addis Ababa, Ethiopia. The study employed a qualitative methodology with an inductive approach and a thematic analysis. It involved in-depth interviews with healthcare workers providing clinical services to DR-TB patients in 10 public healthcare facilities in Addis Ababa, Ethiopia. A total of 18 healthcare workers participated until data saturation, which included 12 clinical nurses, four health officers and two medical laboratory technicians. The findings show that healthcare workers perceive DR-TB as a growing public health threat in Ethiopia, due to factors such as poverty, poor nutrition, crowded settings, healthcare worker and general public awareness of DR-TB, lack of good governance and culture. The perspectives drawn from the healthcare workers shed more light on the image of DR-TB in a developing country context. It has been shown that understanding DR-TB is not confined to what can be drawn from the sphere of biomedicine. There are also interconnected barriers, which predict a dystopia in the epidemiology of DR-TB. Bringing DR-TB under control requires taking a step back from an overwhelming focus on the biomedical facets of the disease, and employ critical thinking on the wider social and structural forces as equally important targets.